Raynaud's phenomenon after radical radiotherapy for tumours of the head and neck. Issue 929 (1st March 2003) - Westbury, C B; Harrington, K J; Rhys-Evans, P; Archer, D J; Searle, A E; Henk, J M; Black, C M; Nutting, C M
Abstract : Endothelial cell injury is implicated in the development of radiation induced tissue damage and may also be involved in the pathophysiology of secondary Raynaud's phenomenon. Two patients are presented in whom the typical symptoms and signs of Raynaud's phenomenon developed as a late complication of radical radiotherapy. One had Raynaud's of the tongue and one of the lip. Both patients had a prior history of primary Raynaud's phenomenon and in each case the symptoms were repeatedly precipitated by sudden cold exposure. The possible pathogenesis of radiation induced Raynaud's phenomenon in the head and neck region is discussed.